Sexual dimorphism in vascular ATP‐sensitive K+ channel function supporting interstitial PO2 via convective and/or diffusive O2 transport. (8th June 2021) - Colburn, Trenton D.; Weber, Ramona E.; Schulze, Kiana M.; Hageman, K. Sue; Horn, Andrew G.; Behnke, Brad J.; Poole, David C.; Musch, Timothy I.
Abstract : Key points: Inhibition of pancreatic ATP‐sensitive K + (KATP ) channels is the intended effect of oral sulphonylureas to increase insulin release in diabetes. However, pertinent to off‐target effects of sulphonylurea medication, sex differences in cardiac KATP channel function exist, whereas potential sex differences in vascular KATP channel function remain unknown. In the present study, we assessed vascular KATP channel function (topical glibenclamide superfused onto fast‐twitch oxidative skeletal muscle) supporting blood flow and interstitial O2 delivery‐utilization matching ( P O 2 is ) during twitch contractions in male, female during pro‐oestrus and ovariectomized female (F+OVX) rats. Glibenclamide decreased blood flow (convective O2 transport) and interstitial P O 2 in male and female, but not F+OVX, rats. Compared to males, females also demonstrated impaired diffusive O2 transport and a faster fall in interstitial P O 2 . Our demonstration, in rats, that sex differences in vascular KATP channel function exist support the tentative hypothesis that oral sulphonylureas may exacerbate exercise intolerance and morbidity, especially in premenopausal females. Abstract: Vascular ATP‐sensitive K + (KATP ) channels support skeletal muscle blood flow ( Q ̇ m ), interstitial O2 delivery ( Q ̇ O 2 )‐utilization ( V ̇ O 2 ) matching (i.e. interstitial‐myocyte O2 flux driving pressure; P O 2 is ) and exercise tolerance. Potential sex differences in skeletal muscle vascular KATP channel function remain largely unexplored. We hypothesized that local skeletal muscle KATP channel inhibition via glibenclamide superfusion (5 mg kg –1 GLI; sulphonylurea diabetes medication) in anaesthetized female Sprague–Dawley rats, compared to males, would demonstrate greater reductions in contracting (1 Hz, 7 V, 180 s) fast‐twitch oxidative mixed gastrocnemius (97% type IIA+IID/X+IIB) Q ̇ m (15 μm microspheres) and P O 2 is (phosphorescence quenching), resulting from more compromised convective ( Q ̇ O 2 ) and diffusive ( D O 2   ) O2 conductances. Furthermore, these GLI‐induced reductions in ovary‐intact females measured during pro‐oestrus would be diminished following ovariectomy (F+OVX). GLI similarly impaired mixed gastrocnemius V ̇ O 2 in both males (↓28%) and females (↓33%, both P  < 0.032) via reduced Q ̇ m (male: ↓31%, female: ↓35%, both P  < 0.020), Q ̇ O 2 (male: 5.6 ± 0.5 vs . 4.0 ± 0.5, female: 6.4 ± 1.1 vs . 4.2 ± 0.6 mL O2  min –1 100 g tissue –1, P  < 0.022) and the resulting P O 2 is, with females also demonstrating a reduced D O 2   (0.40 ± 0.07 vs . 0.30 ± 0.04 mL O2  min –1 100 g tissue –1, P  < 0.042) and a greater GLI‐induced speeding of P O 2 is fall (mean response time: Sex × Drug interaction, P  = 0.026). Conversely, GLI did not impair the mixed gastrocnemius of F+OVX rats. Therefore, in patients taking sulphonylureas, these results support the potential for impaired vascular KATP channel function to compromise muscle Q ̇ m and therefore exercise tolerance. Such an effect, if present, would likely contribute to adverse cardiovascular events in premenopausal females more than males. Key points: Inhibition of pancreatic ATP‐sensitive K + (KATP ) channels is the intended effect of oral sulphonylureas to increase insulin release in diabetes. However, pertinent to off‐target effects of sulphonylurea medication, sex differences in cardiac KATP channel function exist, whereas potential sex differences in vascular KATP channel function remain unknown. In the present study, we assessed vascular KATP channel function (topical glibenclamide superfused onto fast‐twitch oxidative skeletal muscle) supporting blood flow and interstitial O2 delivery‐utilization matching ( P O 2 is ) during twitch contractions in male, female during pro‐oestrus and ovariectomized female (F+OVX) rats. Glibenclamide decreased blood flow (convective O2 transport) and interstitial P O 2 in male and female, but not F+OVX, rats. Compared to males, females also demonstrated impaired diffusive O2 transport and a faster fall in interstitial P O 2 . Our demonstration, in rats, that sex differences in vascular KATP channel function exist support the tentative hypothesis that oral sulphonylureas may exacerbate exercise intolerance and morbidity, especially in premenopausal females.